Test the accuracy of measuring the Qibla direction of mosques and eating in Saotengah Village, Central Sinjai District, Sinjai Regency - Dian Maharany,; Nur Aisyah,; Kiljamiawati, (HISABUNA: Jurnal Ilmu Falak, 2023)
The direction of the Kaaba can be determined from any point or place on the earth's surface by calculation and measurement. The determination of the Qibla direction for mosques and graves in Saotengah Village, Sinjai Tengah District, Sinjai Regency has been carried out by religious leaders using a simple method and different from the method currently used. The majority of people in the area believe that the west direction is the correct Qibla direction. This research is a field study that uses a qualitative approach and involves the disciplines of Astronomy, Syari'i, and Sociology. Sources of data used in this study consisted of primary and secondary data. The purpose of this study was to determine the method of determining the Qibla direction of mosques and tombs in Saotengah Village, Central Sinjai District, Sinjai Regency. Therefore, it is necessary to re-check the position of the Qibla direction in the mosque and the tomb using several methods, such as the Qibla Tracker, Protractor, and Special Stick. This study involved four mosques and two graves as samples in determining the Qibla direction. The results of this study indicate that the accuracy of determining the Qibla direction in mosques and cemeteries is not sufficient. In the measurement, there are three of the four mosques that have deviated from the direction they should be, while in the measurement of the tombs, all of them have deviated. Therefore, it is necessary to socialize from the government, especially the Ministry of Religion, to conduct accuracy and education tests related to the method of determining the Qibla direction of mosques and tombs, and it is hoped that the community, especially religious shops, will be more sensitive and try to find out the Qibla direction determination so that mistakes do not occur or obstacles in determining the Qibla direction.